Effectiveness Of Domestic Preparation Kromoviz In Treatment Of Allergic Conjunctivites - Abdullaevich, Nuraliev Nekkadam; Oripovich, Safarov Jakhongir; Khayotovich, Khasanov Mukhriddin (The American Journal of Medical Sciences and Pharmaceutical Research, 2021)
Purpose: to study the efficacy and tolerability of the domestic drug cromoviz in the treatment of allergic conjunctivitis. The state of the organ of vision in 60 patients (120 eyes) with allergic conjunctivitis was studied. Depending on the therapy, the patients were divided into two groups of homogeneous clinical manifestations. At the same time, the patients of the main group (30 patients) were instilled with the drug Cromoviz (Uzbekistan), 2 drops 4 times a day for 4 weeks. Patients of the control group (30 patients) were instilled with Aycrol according to the same scheme. The obtained research results showed that the use of the domestic drug cromoviz against the background of basic treatment is expressed in a decrease in subjective complaints of patients and a significant clinical effect in 95.9% of cases. The revealed economic efficiency of the drug action indicates the achievement of the maximum level of therapeutic result at an acceptable price for the patient and therapeutic-prophylactic institution. Cases of side effects and intolerance to the domestic drug cromoviz were not identified in our studies.